1995
DOI: 10.1103/physrevlett.74.1264
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Phase Effects for Wave-Packet Revivals

Abstract: The study of wavepacket revivals is extended to the case of Hamiltonians which are made time-dependent through the adiabatic cycling of some parameters. It is shown that the quantal geometric phase (Berry's phase) causes the revived packet to be displaced along the classical trajectory, by an amount equal to the classical geometric phase (Hannay's angle), in one degree of freedom. A physical example illustrating this effect in three degrees of freedom is mentioned.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Not only is the theory firmly based, and simulations convincing, but even an application, based on this phenomenon and aimed at separation of isotopes, has been proposed [199]. Elsewhere, it was shown that the effect of slow cycling on the evolving wave-packet is to leave the revival period unchanged, but to cause a shift in the position of the revived wave packet [200].…”
Section: Aspects Of Phase In Moleculesmentioning
confidence: 99%
“…Not only is the theory firmly based, and simulations convincing, but even an application, based on this phenomenon and aimed at separation of isotopes, has been proposed [199]. Elsewhere, it was shown that the effect of slow cycling on the evolving wave-packet is to leave the revival period unchanged, but to cause a shift in the position of the revived wave packet [200].…”
Section: Aspects Of Phase In Moleculesmentioning
confidence: 99%
“…Most such applications apply to time-independent Hamiltonians, and the observation of cyclic wave packet has been of interest [2,3]. Wave-packet revival was also studied in the context of adiabatic time-dependent Hamiltonians, and the link between Berry's phase and Hannay's angle was confirmed [4]. The purpose of this Letter is to explore GWP dynamics for Hamiltonians with nonadiabatic time dependence, find conditions for the occurrence of cyclic GWP, and demonstrate an explicit connection between the nonadiabatic geometrical phase effects in quantum and classical mechanics.…”
mentioning
confidence: 98%
“…It can be seen that Hannay's angles (13) are defined by the similar one-form connection with the Berry phase in Eq. (7).…”
Section: Hannay's Angle In Bo Composite Systemmentioning
confidence: 97%
“…For the same reason, the contribution of the fast quantum subsystem to φ k is written as the mean value of the one in Eq. (13). For A hyb 2 (m, n; X ), different with the full quantum phase one-form or classical angle one-form, the part…”
Section: Berry Phase and Hannay Angle In Bo Hybrid Systemmentioning
confidence: 98%
See 1 more Smart Citation